A Linear and Stereoselective Approach for the Synthesis of Dapoxetine from Benzaldehyde - Chinta, Ramakoteswara R.; Paridala, Kumaraswamy; Tulam, Vijay Kumar (Letters in Organic Chemistry, 2024)
In addition to providing a succinct pathway for the stereoselective synthesis of dapoxetine, a potent SSRI employed in the treatment of premature ejaculation, this study highlights the strategic use of Ellman's sulfinamide as a chiral auxiliary. The key method involves the diastereoselective allylation of (S,E)-N-Benzylidenesulfinamide, resulting in the desired S-configuration critical for the pharmacological activity of dapoxetine. The utilization of readily available benzaldehyde as the starting material and 1-naphthol as a late-stage coupling partner contributes to the economic feasibility of the synthesis. Especially, the linear synthetic approach adopted in this study employs simplified and more efficient protocols for various transformations, culminating in an overall yield of 26%. This research not only presents a practical synthetic route for dapoxetine, but also underscores the importance of cost-effective and streamlined methodologies in drug development processes.
Keywords: SSRI